Аналіз нормативно-правового забезпечення прав та обов’язків пацієнтів в Україні = Analysis of legal ensuring the rights and responsibilities of patients in Ukraine - Mikhal'chuk, V. M. (Journal of Education, Health and Sport, 2015)
Mikhal'chuk V. M. Аналіз нормативно-правового забезпечення прав та обов’язків пацієнтів в Україні = Analysis of legal ensuring the rights and responsibilities of patients in Ukraine. Journal of Education, Health and Sport. 2015;5(8):474-486. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.31997 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A474-486 https://pbn.nauka.gov.pl/works/652951 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.07.2015. Revised 05.08.2015. Accepted: 24.08.2015. УДК 614.2:341[614.253.8](477) АНАЛІЗ нормативно-правового забезпечення прав та обов’язків пацієнтів в Україні Analysis of legal ensuring the rights and responsibilities of patients in Ukraine В. М. Михальчук V. M. Mikhal'chuk Національна медична академія післядипломної освіти імені П.Л. Шупика Shupyk National Medical Academy of Postgraduate Education Summary The article presents an analysis of regulatory framework of rights and responsibilities of patients inUkraine, the main guarantees and possible solutions in case of violation of the rights of patients. Keywords: legal and regulatory provision, the rights and responsibilities of patients, violation of patients' rights. Резюме Анализ нормативно-правового обеспечения прав и обязанностей пациентов в Украине. В статье изложены результаты анализа нормативно-правового обеспечения прав и обязанностей пациентов в Украине, основные гарантии и возможные пути решения в случае нарушения прав пациентов. Ключевые слова: нормативно-правововое обеспечение, права и обязанности пациентов, нарушене прав пациентов. Резюме В статті викладено результати аналізу нормативно-правового забезпечення прав та обов’язків пацієнтів в Україні, основні гарантії та можливі шляхи вирішення у випадку порушення прав пацієнтів. Ключові слова: нормативно-правове забезпечення, права та обов’язки пацієнтів, порушення прав пацієнтів.